2017
DOI: 10.18203/2319-2003.ijbcp20174376
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of awareness about pharmacoeconomics in postgraduate students of a tertiary care teaching hospital: a questionnaire based observational study

Abstract: Background: Pharmacoeconomics identifies, measures and compares the costs and consequences of drug therapy to health care systems and society. The per capita income of all middle class people is limited and the drug prices are growing extensively. Therefore, it is the responsibility of the health-care professionals to balance both cost and quality of treatment. Hence, this study was planned among the postgraduate students who form the major part of health care delivery system to assess their awareness about ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…19 Pharmacoeconomics can act as a decision-making aid for healthcare professionals to improve the cost-efficiency and equity of resource allocation, consequently reducing the economic burdens on patients and third-party payers, such as the government. 3,[6][7][8] Previous studies, such as that by Al-Jazairi et al, 1 showed that some barriers challenge the application of pharmacoeconomics for decisionmaking, such as the lack of quality data on the Saudi population and scarce clinically relevant and unbiased published costeffectiveness data when a new drug is considered for addition to the formulary. However, this study shows that pharmacists, who are key resource allocators in healthcare, have suboptimal awareness and knowledge of pharmacoeconomics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19 Pharmacoeconomics can act as a decision-making aid for healthcare professionals to improve the cost-efficiency and equity of resource allocation, consequently reducing the economic burdens on patients and third-party payers, such as the government. 3,[6][7][8] Previous studies, such as that by Al-Jazairi et al, 1 showed that some barriers challenge the application of pharmacoeconomics for decisionmaking, such as the lack of quality data on the Saudi population and scarce clinically relevant and unbiased published costeffectiveness data when a new drug is considered for addition to the formulary. However, this study shows that pharmacists, who are key resource allocators in healthcare, have suboptimal awareness and knowledge of pharmacoeconomics.…”
Section: Discussionmentioning
confidence: 99%
“…First, subgroup analysis based on gender showed that women scored higher in both awareness and knowledge than men (2.44 and 2.37 versus 1.69 and 1.23, respectively). Moreover, those who occupied administrative positions scored lower in both 12 (7) awareness and knowledge than those who had never held an administrative position (1.63 and 1.28 versus 2.04 and 1.72, respectively), even though administrators are supposed to be decision-makers. Nearly 84% of participants who had held administrative positions had more than five years of experience, while only 32% of those who had never held administrative positions had more than five years of experience.…”
Section: Subgroup Analysesmentioning
confidence: 91%
See 2 more Smart Citations